Moderately Hypofractionated Radiotherapy and Androgen Deprivation Therapy for High-risk Localised Prostate Cancer: Predictors of Long-term Biochemical Control and Toxicity. Issue 1 (January 2022) - Maulik, S.; Arunsingh, M.; Arun, B.; Prasath, S.; Mallick, I.
Abstract: Aims: There is a paucity of long-term data on outcomes of high-risk prostatic adenocarcinoma after moderately hypofractionated radiotherapy with elective nodal treatment and long-term androgen deprivation therapy (ADT). We report long-term control and toxicity outcomes and analyse the predictors of failure and toxicity. Materials and methods: The records of 120 consecutive high-risk prostate cancer patients treated in a single institution between February 2012 and December 2016 were retrospectively analysed. A moderately hypofractionted radiotherapy (HypoRT) regimen of 60 Gy in 20 fractions over 4 weeks with simultaneous elective pelvic irradiation to 44 Gy in 20 fractions with intensity-modulated radiotherapy was used, together with long-term ADT with either orchiectomy or medical castration for a total duration of 2–3 years. We analysed biochemical control, metastasis-free survival and late toxicities and their predictive factors using survival analysis. Results: Patients had locally advanced cancers (cT3 77.5%, median pretreatment prostate-specific antigen 30 ng/ml, Gleason score 8–10 in 45.8%). The median follow-up time was 70 months. The 3- and 5-year probability of freedom from biochemical progression was 93% and 80%, respectively. The 5-year probability of freedom from local relapse/intra-pelvic nodal relapse/distant metastases as the site of first failure was 96%/97%/86%, respectively. Gleason score 8–10 and medical ADT for 2–3 years (as opposed to orchidectomy) were independent risk factors for distant metastases. A total of 18 grade 2 and above late gastrointestinal toxicity events and a total of 23 grade 2 and above late genitourinary toxicity events were documented. Patients who underwent a transurethral resection of prostate prior to radiotherapy had worse urological toxicity. Conclusions: HypoRT with elective nodal treatment results in excellent pelvic control. Distant metastases are the primary mode of failure. Risk of metastases is associated with Gleason score and the duration of ADT. Late urinary toxicities are more common in those with prior transurethral resection of prostate. Highlights: Moderate hypofractionation is implementable in high-risk localised prostate cancer. Pelvic control is excellent, and most failures manifest as distant metastases. Metastasis-free survival is longer with orchidectomy versus 2–3 years of medical castration. Metastasis-free survival is longer in patients with Gleason 6–7 versus Gleason 8–10.